The Uses and Abuses of Moral Theory in Bioethics - De Vries, Raymond (Ethical theory and moral practice, 2011)
Moral theory is an important guide to bioethical decision-making, but it can confuse and mislead those who offer ethical advice to clinicians and researchers, delaying decisions that must be made in a timely fashion. In this paper I examine the ways moral theory can lead bioethicists astray. Absent a sensitivity to the empirical realities of ethical problems, moral theory 1) contributes to the disappearance of the persons caught in an ethical quandary, 2) focuses on the puzzle-solving rather than examining the conditions that generate moral problems, and 3) universalizes ethical dilemmas, overlooking local processes for resolving moral questions. Taken together, empirically informed moral theory and theoretically informed empirical research can help bioethicists transcend the is/ought problem in ethical work.